SCADA Systems, Applications in Water Treatment Plants along the Ecuadorian Coast Region, Case study: El Empalme Municipality - Amaya Jaramillo , Carlos David (2025)
This work describes the design of a SCADA system to improve the drinking water service in the municipality of El Empalme Canton, Ecuador. It outlines the design phases, criteria for analyzing the automation status of the plant, automation design, and device selection. The SCADA system, which uses PLCs, sensors, and pumps connected via the ModBus TCP protocol, enhanced operational efficiency, reduced response times, and contributed to the quality of the final product. Issues such as imbalances in panel protections and extended response times were addressed through simulation of the automation model.